Problems of Da’wah in Social Media in Gorontalo City Communities - Thaib, Erwin Jusuf (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2019)
This study reveals how the reality of da’wah on social media in the people of Gorontalo City, how is the problem of da'wah on social media, and what are the implications of this problem for the future of Islamic da'wah. Through this study, it will be illustrated how social media acts as a medium of da'wah and the problems that occur in it. The results of this qualitative research revealed that besides being used as a means of entertainment and interaction, social media was also used as a medium of da’wah. In general, da’wah on social media such as the implementation of da'wah in the real world even though it is packaged differently. Even so, da’wah on social media has a distinctive form that is in accordance with the character of social media itself, namely in the form of writing and drawing. The problematic da’wah on social media in the people of Gorontalo City is more visible in cyberspace than in the real world. This problem is driven by two main factors, namely the material of da'wah which is inconsistent and vulnerable to infiltration by other elements outside the da'wah and the figure of the prosecutor himself who lacks the scientific capacity to da’wah and has an exclusive religious character that tends to give birth to conflict. The problem of da’wah on social media will be dangerous if it is not resolved completely because it will have negative implications for the future of da'wah itself. The problem of da'wah on social media will cause people to be unsympathetic to Islamic da'wah and cause da'wah to lose opportunities to take advantage of the progress of the times for the development of da'wah. Penelitian ini mengungkapkan bagaimana realitas dakwah di media sosial di masyarakat Kota Gorontalo, masalah dakwah di media sosial, dan apa implikasi dari masalah ini bagi masa depan dakwah Islam. Melalui penelitian ini, diilustrasikan bagaimana media sosial bertindak sebagai media dakwah dan masalah apa saja yang terjadi di dalamnya. Hasil penelitian kualitatif ini mengungkapkan bahwa selain digunakan sebagai sarana hiburan dan interaksi, media sosial juga digunakan sebagai media dakwah. Secara umum, dakwah di media sosial sama seperti penerapan dakwah di dunia nyata meski dikemas berbeda. Meski begitu, dakwah di media sosial memiliki bentuk khas yang sesuai dengan karakter media sosial itu sendiri, yaitu dalam bentuk tulisan dan gambar. Dakwah yang bermasalah di media sosial di masyarakat Kota Gorontalo lebih terlihat di dunia maya daripada di dunia nyata. Masalah ini didorong oleh dua faktor utama, yaitu bahan dakwah yang tidak konsisten dan rentan terhadap infiltrasi oleh unsur-unsur lain di luar dakwah dan sosok da’i sendiri yang tidak memiliki kapasitas ilmiah untuk berdakwah dan memiliki karakter religius eksklusif yang cenderung melahirkan konflik. Masalah dakwah di media sosial akan berbahaya jika tidak diselesaikan sepenuhnya karena akan berdampak negatif bagi masa depan dakwah itu sendiri. Masalah dakwah di media sosial akan menyebabkan orang tidak simpatik pada dakwah Islam dan menyebabkan dakwah kehilangan kesempatan untuk mengambil keuntungan dari perkembangan zaman untuk pengembangan dakwah.